COQ8B glomerular nephropathy: Outcomes after kidney transplantation and analysis of characteristics in Chinese population - Zeng, Shuhan; Xu, Yuanyuan; Cheng, Cheng; Yu, Nannan; Liu, Longshan; Mo, Ying; Chen, Lizhi; Jiang, Xiaoyun (Frontiers in Pediatrics, 2022)
Background Mutation in the COQ8B gene can cause COQ8B glomerular nephropathy (COQ8B-GN), which is rare and associated with steroid-resistant nephrotic syndrome (SRNS) as well as rapid progression to end-stage renal disease (ESRD). The aim of this study was to analyze the prognosis and recurrence risk of COQ8B-GN in patients after kidney transplantation (KTx) and summarize the characteristics of the Chinese population. Methods A retrospective study included four cases treated in our hospital with a diagnosis of COQ8B-GN. Chinese and foreign studies were searched from database inception to February 2022. Results A total of four cases were included, with the age of onset ranging from 4 to 9 years. The initial presentations were SRNS and asymptomatic proteinuria. Only one had an extrarenal manifestation (thyroid cyst). All patients progressed to ESRD at a mean time of 42 months after onset. With a total follow-up time ranging from 12 to 87 months, three of them had received transplantation. While one case needed a second KTx due to graft failure caused by chronic rejection, two recipients had excellent graft function. No recurrence in allograft was observed. There have been 18 cases of KTx recipients reported globally with follow-up information. Except for two cases of graft failure caused by hyperacute rejection and chronic rejection, respectively, the rest all had good graft function without recurrence. In addition, 44 cases of COQ8B-GN in the Chinese population were identified. At the onset, 75% of the patients were aged ≤10 years with initial symptoms of asymptomatic proteinuria, nephrotic syndrome (NS), or SRNS. By the time of literature publication, 59% of patients had progressed to ESRD (mean age of 10.3 ± 3.6 years). The median time from onset to ESRD was 21 months. Renal pathology mainly showed focal segmental glomerulosclerosis (FSGS), accounting for 61.8% of all biopsies, followed by mesangial proliferative glomerulonephritis (20.6%). The first three prevalent mutations in the COQ8B gene among the Chinese population were c. 748G>C, c. 737G>A, and c. 532C>T. Conclusion COQ8B-GN in the Chinese population may present with asymptomatic proteinuria, NS, or SRNS initially, with most onsets before the age of 10 years. A lot of patients progress to ESRD in early adolescence. FSGS on biopsy and c. 748G>C in the genetic test are the most frequently seen in Chinese COQ8B-GN patients. KTx is feasible for patients with ESRD due to the low risk of recurrence, but we should pay attention to graft rejection.